Creating A Customer Retention System for A Traditional Restaurant Business for The Success of The Organization - Kanakasai, Chakarat; Muangsan, Uthairat (Rajapark Journal, 2022)
The purpose of this research was to study the causal factors of Service marketing mix of information technology and social marketing That affects the retention of customers. To study the causal factors of Service marketing mix information technology and social marketing that affect the modern business operation of the traditional restaurant business for the success of the organization. and to model the customer retention system of the traditional restaurant business for corporate success. The participants were 544 people who were Restaurant business operators in Thailand by stratified sampling. The research instrument was a questionnaire. The statistics used to analyze the data were mean, standard deviation, and using the Structural Equation Model with Partial Least Squares technique for testing hypotheses. The findings revealed that service marketing mix factor information technology factor Social Media Marketing Factors That affect the retention of customers in the traditional restaurant business for the success of the organization the overall level is at a high level. In customer retention studies and modern business operations, the overall level is at a high level. and modeling on building customer retention systems of traditional restaurant businesses for corporate success found that the structural equation modeling model was appropriate to blend with the empirical data. The research highlights the importance of understanding the influence and causal relationship patterns of building a traditional restaurant customer retention system for corporate success.